Establishment of Monoclonal Antibody PMab-202 Against Horse Podoplanin - Furusawa, Yoshikazu; Yamada, Shinji; Itai, Shunsuke; Sano, Masato; Nakamura, Takuro; Yanaka, Miyuki; Handa, Saori; Mizuno, Takuya; Maeda, Ken; Fukui, Masato; Harada, Hiroyuki; Kaneko, Mika K; et al. (Monoclonal antibodies in immunodiagnosis and immunotherapy, 2018)
Podoplanin (PDPN), a type I transmembrane glycoprotein, is expressed in several body tissues, including podocytes of renal glomerulus, type I alveolar cells of lung, and lymphatic endothelial cells. PDPN activates platelet aggregation by binding to C-type lectin-like receptor-2 (CLEC-2) presented on platelets. Monoclonal antibodies (mAbs) against human-, mouse-, rat-, rabbit-, dog-, bovine-, and cat-PDPN have already been established. However, anti-horse PDPN mAbs have not yet been developed. In this study, we immunized mice with synthetic horse PDPN peptides and developed anti-horse PDPN mAbs. One of the established mAbs, PMab-202 (IgG , kappa), was specifically able to detect horse PDPN in Chinese hamster ovary/horse PDPN (CHO/horPDPN) cells in flow cytometry experiments. PMab-202 was also able to detect endogenous horse PDPN expressed in and a horse kidney cell line, FHK-Tcl3.1, in flow cytometry and Western blot analyses. PMab-202 is expected to prove useful in investigating the function of horse PDPN.